1987
DOI: 10.1128/aac.31.8.1238
|View full text |Cite
|
Sign up to set email alerts
|

Antiherpesvirus activity of 9-(4-hydroxy-3-hydroxy-methylbut-1-yl)guanine (BRL 39123) in cell culture

Abstract: The activity of 9-(4-hydroxy-3-hydroxymethylbut-1-yl)guanine (BRL 39123) against several herpesviruses was compared with that of acyclovir (ACV). In plaque reduction tests with clinical isolates of herpes simplex virus type 1 (HSV-1), herpes simplex virus type 2 (HSV-2), and varicella-zoster virus, mean 50% inhibitory concentrations (IC50s) (n = number tested) for BRL 39123 were 0.4 (n = 17), 1.5 (n = 13), and 3.1 (n = 5) ,ug/ml, respectively. Corresponding IC50s for ACV were 0.2, 0.6, and 3.8 ,ig/ml. Cytomega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(86 citation statements)
references
References 25 publications
5
79
0
2
Order By: Relevance
“…The concentration of 2-HM or acyclovir that produced a 50 % reduction in plaque numbers (ICs0 value) was determined ( Table 1). The ICs0 obtained for acyclovir against VZV in these assays was in agreement with results reported elsewhere using MRC5 cells (Boyd et al, 1987) and was similar to that observed for 2-HM. The appearance and stain uptake of cells was unaltered even with 80 ~tM-2-HM.…”
Section: Inhibition Of Varicella-zoster Virus Replication By An Inhibsupporting
confidence: 81%
“…The concentration of 2-HM or acyclovir that produced a 50 % reduction in plaque numbers (ICs0 value) was determined ( Table 1). The ICs0 obtained for acyclovir against VZV in these assays was in agreement with results reported elsewhere using MRC5 cells (Boyd et al, 1987) and was similar to that observed for 2-HM. The appearance and stain uptake of cells was unaltered even with 80 ~tM-2-HM.…”
Section: Inhibition Of Varicella-zoster Virus Replication By An Inhibsupporting
confidence: 81%
“…15 Famciclovir was originally approved for the treatment of herpes simplex virus and herpes zoster virus. 16,17 Later, famciclovir was shown to have activity against human and duck hepatitis B viruses in enzymatic and cell culture assays and in animal models of infection. 15,[18][19][20][21] Clinical studies subsequently showed that famciclovir can reduce serum HBV levels in patients chronically infected with HBV.…”
mentioning
confidence: 99%
“…With the discovery of acyclovir (ACV) in 1974 (11) and later of penciclovir (PCV) (12), antiviral therapy was revolutionized. These guanine analogues are highly selective in fighting active HSV outbreaks because of their specific mode of action and activation.…”
Section: Standard Treatment Of Herpes Simplex Virus Infectionsmentioning
confidence: 99%